The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3109/23744235.2015.1133926
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare workers mobile phone usage: A potential risk for viral contamination. Surveillance pilot study

Abstract: Mobile phones in clinical practice may be contaminated with viral pathogenic viruses. HCWs use their mobile phone regularly while working and, although the majority are aware of contamination, they do not disinfect their phones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 19 publications
3
35
0
Order By: Relevance
“…Except for bacterial contamination, Candida spp. [ 30 ] or even viruses [ 31 ] can also be transmitted by the mentioned devices.…”
Section: Discussionmentioning
confidence: 99%
“…Except for bacterial contamination, Candida spp. [ 30 ] or even viruses [ 31 ] can also be transmitted by the mentioned devices.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, 10% of phones which were tested had viral pathogens. 17 Studies have also reported medical students to have four times higher odds of having heavy growth of microbes on their mobile phones. 11 These findings are particularly important, given the evidence in a recent review, which included 22 studies, that coronavirus can survive on inanimate surfaces like metal, glass or plastic surface for 2 hours to 9 days, and that high temperature such as 30°C or 40°C reduced the duration of persistence.…”
Section: Covid-19 Mobile Phones and Disease Epidemiologymentioning
confidence: 99%
“…Hospital environment is one of the most favorable for colonization of air and environmental objects with conditionally pathogenic and pathogenic microorganisms [10,11]. Via airborne, community-acquired, fecal-oral routes and transmissions, causative agents of infectious diseases get into environment of medical organizations from patients [10].…”
mentioning
confidence: 99%
“…Hospital environment is one of the most favorable for colonization of air and environmental objects with conditionally pathogenic and pathogenic microorganisms [10,11]. Via airborne, community-acquired, fecal-oral routes and transmissions, causative agents of infectious diseases get into environment of medical organizations from patients [10]. Ac-cumulation and circulation of microorganisms in the air and on the objects of medical premises can subsequently become a source of healthcare-associated infections (HAI) [1,3,10,13].…”
mentioning
confidence: 99%
See 1 more Smart Citation